ARIMA MODELS IN PREDICTING INDONESIAN ISLAMIC BANK PROFITABILITY - Muhammad Hakim Sitompul; T. Rizkan Polem; Dede Ruslan; Muhammad Fitri Rahmadana (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to predict the profitability of Bank Muamalat Indonesia, proxied by the ROA ratio. The data analysis used is ARIMA (Autoregressive Integrated Moving Average), which is an appropriate approach for analyzing time series data such as the profitability of Bank Muamalat Indonesia over the period 2010-2023. The findings indicate that the ARIMA (1,1,12) model is the best in predicting the profitability of Bank Muamalat Indonesia. This is because the ARIMA (1,1,2) model demonstrates white noise characteristics and produces low AIC and SC values as well as significant parameters, thus it is selected for analysis. Using the ARIMA (1,1,2) model, profitability estimation shows RMSE values of 0.39 and MAE values of 0.32, indicating a low error rate. The prediction shows a significant decline in the profitability of Bank Muamalat Indonesia, although fluctuations remain. Therefore, the ARIMA (1,1,2) model proves to be effective in predicting the profitability of Bank Muamalat Indonesia with a low error rate, despite the prediction results showing a downward trend.